Interprofessional education in cancer care - a scoping review - Sulosaari, Virpi; Dodlek, Nikolina; Brandl, Andreas; De Munter, Johan; Eriksen, Jesper Grau; McInally, Wendy; O’Higgins, Niall; Benstead, Kim; Díez de los Ríos de la Serna, Celia (BMC medical education, 2024)
Comprehensive cancer care requires effective collaboration by interprofessional healthcare teams. The need to develop educational initiatives to improve interprofessional collaboration is increasingly recognised. However, there is no agreement regarding the interprofessional competencies required for effective cancer care leading to much variation on the focus of research, planning and managing change. A scoping review was conducted to identify the current status of IPE in cancer care and to summarise the results of previous research in order to guide the development of interprofessional education in cancer care.
Online veröffentlicht: 16. Juli 2024
Gesehen am 03.02.2025